Reconstruction of past variation in lake water balance at upstream Smoky and Wabasca watersheds to improve understanding of causes of lake drying in the Peace-Athabasca Delta - Thibault, Hannah (University of Waterloo, 2023)
Controversy persists regarding causes of recent lake-level drawdown within the internationally recognized Peace-Athabasca Delta (PAD), northern Alberta. Central to this debate are conflicting interpretations of causes of decline in Lower Peace River ice-jam flood frequency that has led to reduced flooding of lakes and water-level drawdown across the delta. On one hand, studies analyzing Peace River hydrometric data and Traditional Knowledge and historical records of ice-jam flood frequency have attributed lake drying to decreased ice-jam flood frequency caused by the W.A.C. Bennett Dam, which has regulated Peace River flow since 1968. Statistical analysis of these records has also been used to establish a hypothesis that ice-jam flood frequency was accelerating prior to construction of the dam and declined thereafter. In contrast, paleolimnological analyses of sediment cores from oxbow and perched lakes in the Peace sector of the PAD identified declining ice-jam flood frequency and lake drying since the late 1800s and attributed this to a shifting climate following the Little Ice Age. Further investigation is needed to delineate influences of climate versus Peace River flow regulation and reconcile contrasting interpretations of the timing and causes of declining ice-jam flood occurrence along the Lower Peace River and lake drying at the PAD. Reconstructing climate-driven hydrological change at the upstream unregulated Smoky and Wabasca watersheds, which provide substantial discharge to the Peace River when ice-jam floods occur at the PAD, may add critical insight into causes of hydrological change at the PAD. Recent analyses of sediment cores from oxbow lakes within the watersheds of these ‘trigger tributaries’ have revealed that flood influence began to decline decades before operation of the W.A.C. Bennett Dam, coincident with decline of ice-jam flood occurrence at the Lower Peace River and lake drying in the PAD (Girard, 2022; Stratton, 2022). Here, paleolimnological analyses of sediment cores from remote, ...